If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 1) + 2(x + -3) = 13 Reorder the terms: 5(1 + x) + 2(x + -3) = 13 (1 * 5 + x * 5) + 2(x + -3) = 13 (5 + 5x) + 2(x + -3) = 13 Reorder the terms: 5 + 5x + 2(-3 + x) = 13 5 + 5x + (-3 * 2 + x * 2) = 13 5 + 5x + (-6 + 2x) = 13 Reorder the terms: 5 + -6 + 5x + 2x = 13 Combine like terms: 5 + -6 = -1 -1 + 5x + 2x = 13 Combine like terms: 5x + 2x = 7x -1 + 7x = 13 Solving -1 + 7x = 13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 7x = 13 + 1 Combine like terms: -1 + 1 = 0 0 + 7x = 13 + 1 7x = 13 + 1 Combine like terms: 13 + 1 = 14 7x = 14 Divide each side by '7'. x = 2 Simplifying x = 2
| 10x+10=10x+10 | | (-2)=4x^2-2x-25 | | 15x-56x=x^2 | | 4-.025x=.1-.05x | | 3x^2-13x+4= | | 3x+8-5x=12 | | 4x^2+8x-35=0 | | 2+3x=9x-34 | | -18=-2/5(15n-45) | | x+7=x+4 | | 3(x+5)+4(x-3)=17 | | .3x-5.5=.2x+2.6 | | 2x+3(3x+2)=17 | | 6[4(8-4)-5(9+3y)]-21=7[3(7+4y)-4] | | 4+(3+n)=9 | | 7(3n-4)=(7n+7)+5 | | 3b-8=-6+d | | 6n=96 | | 6[4(8-4)-5(9+39)]-21=7[3(7+4y)-4] | | 6(x+5)=5(x-6)+x | | 7x-5=4(x+1)+3x-9 | | 9n=96 | | (3+x+7)+1= | | x+5=-6x+75 | | m^3+20m^2+100m=0 | | 7X+9Y=4 | | 4x+21=12x+51 | | 3n^2-48n+192=0 | | t^2-40t-64=0 | | 5*5*x*x*x= | | -12-4x+5=4x+12 | | 9r-7=15r-(4r+23) |